Outcomes of Religion and Faith on Mental Health among the Seventh-day Adventists in Africa - Ganu, Daniel (British Journal of Healthcare and Medical Research, 2024)
Numerous studies have linked and synchronized religious experiences with positive mental health. Despite the prevalence of mental health concerns, there is still a stigma attached to mental illness in many of the Seventh-day Adventist (SDA) churches in Africa. The predominant culture of silence, along with mistaken expectations and misguided attitudes, often causes suffering believers to feel ashamed, blamed, and alone in their experience of mental illness. This study aimed to assess the SDA church members’ mental health in Africa. The paper summarized some of the most important factors that were found to correlate with the religious and mental health experiences of the SDA church in the continent of Africa. The study utilized a cross-sectional design and quantitative data collection method. The 213-item questionnaire contained closed and open-ended items and was administered by trained research assistants. The study revealed that married people in the church tend to have more positive mental health than those who are single, separated, divorced, or widowed, and older people tend to have more positive mental health than younger people (p<.05). Moreso, the older age group demonstrated more positive mental health compared with the younger age group (p < 0.01) in the church. Furthermore, 80.6% and 87.3% of the participants have never had any form of depression or suicidal thoughts, respectively. The demonstration of positive general mental health status by the church members in the continent of Africa has positive implications for the health principles taught by the church.